Method for manufacturing solid oxide electrolyte of lithium battery
Through the staged treatment method, in the manufacturing process of solid electrolyte of lithium batteries, the La2Zr2O7 mesophase is formed and the lithium source molecules are added to form LLZO particles with cubic lattice, which solves the problem of difficult to control the loss of lithium source and the complexity of crystal phase, and improves the process yield and cost.
Patent Information
- Application Number
- CN202410690674.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2024-05-30
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, when manufacturing solid oxide electrolytes of lithium batteries, the absence of oxygen or insufficient energy during the sintering process leads to complex crystal phases in the product, which is difficult to control, and extending the sintering time or increasing the sintering temperature will accelerate lithium source loss and affect product stability.
Using the staged treatment method, in the first stage, nitrogen argon reaction sintering is carried out in the lithium-free source molecule and oxygen environment to form a stable La2Zr2O7 mesophase; in the second stage, lithium-source molecule is added and oxygen environment to undergo aerobic reaction sintering, forming LLZO particles with cubic crystal lattice.
It avoids the problems of difficult to control the loss of lithium source and crystal phase complexity, improves the process yield and cost, and ensures the stability and performance of the solid electrolyte of lithium batteries.
Smart Images

Figure CN119601779A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a method for manufacturing a solid oxide electrolyte for a lithium battery. Background Art
[0002] Traditionally, compounds such as zirconium dioxide (ZrO2), lanthanum oxide (La2O3), and lithium carbonate (Li2CO3) are used to manufacture solid electrolytes for lithium batteries by placing a mixed slurry of the three initial compounds of zirconium dioxide (ZrO2), lanthanum oxide (La2O3), and lithium carbonate (Li2CO3) in a ball mill for mixing and grinding in a certain proportion, and then sintering them once with oxygen during the reaction.
[0003] However, during the sintering process, due to the different temperature and phase transformation conditions between powder lumps, some oxides will have oxygen deficiency or insufficient energy, resulting in the inability to form the correct phase (cubic phase), making the phase transformation process chaotic and inconsistent, resulting in the final product containing tetragonal, cubic, and octagonal lattices (the crystal structure composed of tetragonal lattices has a poor efficiency in conducting lithium ions); in this case, most processes use extended sintering time, increased sintering temperature, or both as an adjustment method; however, the above adjustment methods are difficult to single the complex crystal phase, and the extended sintering time and increased sintering temperature often accelerate the loss of lithium sources, and even cause the originally stable octagonal crystal lithium lanthanum zirconium gallium aluminum molecular compound (LLZO) to degrade due to lithium deficiency! To overcome this problem, most developers have supplemented the lithium source for LLZO, making the process lengthy and causing excessive material and energy loss, which is not conducive to production and product control, and makes it difficult to market the product; this problem is particularly obvious when the sintering batch is large.
[0004] Therefore, the prior art has defects and needs to be improved. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for manufacturing a solid oxide electrolyte for lithium batteries, which avoids lithium source loss and the situation of complex and difficult to control crystal phases through staged processing, and designs a new reaction process to solve the defects in the above-mentioned prior art.
[0006] The technical solution of the present invention is as follows: a method for manufacturing a solid electrolyte oxide for lithium batteries is provided, in which there is no lithium source molecule and oxygen environment in the first stage reaction, and nitrogen and argon form an atmosphere for sintering protection. Therefore, even if the internal particles react unevenly or are heated unevenly, the La2Zr2O7 generated by the faster reaction will not further react with oxygen and lithium source molecules to form a mixed crystal phase in the next step, and the first stage obtains a stable La2Zr2O7 intermediate phase; and in the second stage reaction, lithium source molecules and oxygen environment are added, and because the initial intermediate product has a stable and uniform phase, it can react evenly with the reactants to produce LLZO particles with a cubic lattice. In addition, because there is no traditional lithium salt (lithium source molecule) in the first stage, it avoids the lithium consumption caused by cumbersome or lengthy sintering; avoids the phase degradation and disintegration caused by the variation of the equivalent number under sintering; and improves the process yield controllability and cost. Furthermore, in the second stage reaction operation, the small-sized mixture particles are secondary agglomerated and placed in the grid grooves. Since the small-sized mixture particles are secondary agglomerated and dispersed in many tiny storage grids, the reaction rate with oxygen is increased.
[0007] In order to solve the above problems, this case proposes a method for manufacturing a solid electrolyte oxide for a lithium battery, which comprises the following steps:
[0008] At least one first-class salt compound is placed in a first grinder, and then subjected to the first reduced pressure concentration, followed by the first stage of oxygen-free reaction sintering operation; a first mass compound is obtained, and then; the first mass compound is mixed with at least one second salt compound, placed in a second grinder, and then subjected to the second reduced pressure concentration, followed by the second stage of oxygen-containing reaction sintering operation to obtain a second mass compound; the second mass compound is then placed in a third grinder, ground and concentrated under reduced pressure for the third time to obtain the final lithium battery solid electrolyte oxide. The at least one first-class salt compound is a zirconium source compound and a lanthanum source compound; and the at least one second-class salt compound is a lithium source compound, a gallium source compound, an aluminum source compound, and a lanthanum source compound, and the lithium battery solid electrolyte oxide is LLZO. The first grinder and the second grinder are ball mills, and the third grinder is an air flow mill; the first reduced pressure concentration and the second reduced pressure concentration are oil bath reduced pressure concentration, and the third reduced pressure concentration is water bath reduced pressure concentration. The first grinding machine is first loaded with deionized water and methanol; the second grinding machine is first loaded with deionized water; and the third grinding machine is first loaded with anhydrous ethanol. The method comprises the following steps: Step 500: Take a first ball mill, and load deionized water and methanol into the first ball mill; Step 510: Load two initial compounds, i.e., solids, of zirconium source compound and lanthanum source compound into the first ball mill, which have a certain ratio with the original deionized water and methanol, and use a plurality of zirconium beads to mix and grind to form a mixture particle, so that the particle size is less than a specific size; Step 520: Dry the mixture particle through an oil bath vacuum concentrator, so that the deionized water and methanol in the mixture particle are evaporated, so that a plurality of micropores are generated in the dried mixture particle; Step 530: Perform the first stage nitrogen-argon reaction operation, firstly, the mixture obtained in step 520 is The mixture particles are placed in a sintering furnace and continuously heated in a sintering environment with nitrogen and argon. At this time, the mixture particles will undergo a chemical reaction under the protection of the nitrogen and argon sintering in the first stage to produce zirconium-lanthanum compounds; step 540: the zirconium-lanthanum compound is then placed in a second ball mill containing deionized water, and a lithium source compound, a gallium source compound, an aluminum source compound, and a lanthanum source compound are added. A plurality of zirconium beads are used in the second ball mill for mixing and grinding, so that the particle size is less than 1000 nanometers, and small-sized mixture particles are obtained; step 550: then concentrated and dried by the oil bath type decompression concentrator, so that the deionized water in the small-sized mixture particles is completely evaporated, so that a plurality of micro holes are generated on the surface, and the small-sized mixture particles are secondary agglomerated, i.e., sintered powder;Step 560: Perform the second stage of aerobic reaction operation. At this time, in the secondary agglomeration of the small-sized mixture particles, the remaining lithium source compound, the gallium source compound, the aluminum source compound, the lanthanum source compound and O2 will perform the second stage of aerobic reaction operation with the zirconium-lanthanum compound in the first stage reaction, and continue to heat and heat to form modified LLZO particles; because the gallium source compound and the aluminum source compound have higher charge and atomic size, the cubic lattice formed by the entire modified LLZO particles, and the overall crystal structure thereof can produce a larger lithium ion channel, thereby accelerating the conduction rate of lithium ions in the solid electrolyte; wherein the modified LLZO particles will condense into a plurality of agglomerates, i.e., form LLZO agglomerates, each LLZO agglomerate containing a cubic lattice formed by a plurality of modified LLZO particles; Step Step 570: Then the LLZO agglomerate formed by the modified LLZO particles is placed in a jet mill for grinding to form a plurality of modified LLZO fine blocks, wherein anhydrous ethanol is placed in the jet mill and added to the modified LLZO agglomerate to form a solvent containing the LLZO agglomerate; Step 580: Then the modified LLZO fine block is placed in a water bath decompression concentrator for water bath concentration so that the anhydrous ethanol is evaporated to obtain the final LLZO powder; wherein the zirconium source compound is selected from one of zirconium nitrate, zirconium dioxide, and zirconium hydroxide; the lanthanum source compound is selected from one of lanthanum nitrate, lanthanum oxide, and lanthanum hydroxide; the lithium source compound is selected from one of lithium nitrate, lithium carbonate, and lithium hydroxide; the gallium source compound is selected from one of gallium nitrate, gallium oxide, and gallium hydroxide; the aluminum source compound is selected from one of aluminum oxide, aluminum hydroxide, and aluminum nitrate. ;
[0009] By adopting the above scheme, the present invention provides a method for manufacturing lithium battery solid electrolyte oxide, which has the following technical effects: in the first stage reaction, because there are no lithium source molecules and oxygen environment, and nitrogen and argon form an atmosphere for sintering protection, even if the internal particles react unevenly or are heated unevenly, the La2Zr2O7 generated by the faster reaction will not further react with oxygen and lithium source molecules to form a mixed crystal phase in the next step, and the first stage obtains a stable La2Zr2O7 intermediate phase; and in the second stage reaction, lithium source molecules and oxygen environment are added, because the initial intermediate product has a stable and uniform phase, it can react evenly with the reactants to produce LLZO particles with a cubic lattice. In addition, because there is no traditional lithium salt (lithium source molecule) in the first stage, it avoids the lithium consumption caused by cumbersome or lengthy sintering; avoids the phase degradation and disintegration caused by the variation of the equivalent number under sintering; and improves the process yield controllability and cost. Furthermore, in the second stage reaction operation, the small-sized mixture particles are secondary agglomerated and placed in the grid grooves. Since the small-sized mixture particles are secondary agglomerated and dispersed in many tiny storage grids, the reaction rate with oxygen is increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 A flowchart showing the steps in this case.
[0011] Figure 2 A flow chart showing the formation of compound particles in this case.
[0012] Figure 3 A flow chart showing the formation of small-sized compound particles in the present case.
[0013] Figure 4 A flow chart showing the formation of LLZO powder in this case.
[0014] Figure 5 Shows the grille slot structure diagram of this case. DETAILED DESCRIPTION
[0015] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0016] refer to Figures 1 to 5 As shown, Figure 1 The flowchart of the steps of this case shows the method of manufacturing a solid electrolyte oxide for lithium batteries of this invention, which comprises the following steps:
[0017] like Figure 2 As shown, a first ball mill 100 is taken, wherein deionized water and methanol are placed in the first ball mill 100 (step 500).
[0018] The zirconium source compound is selected from zirconium nitrate, zirconium dioxide and zirconium hydroxide. The lanthanum source compound is selected from lanthanum nitrate, lanthanum oxide and lanthanum hydroxide.
[0019] The two initial compounds (i.e., solids) of the zirconium source compound and the lanthanum source compound are placed in the first ball mill and mixed with the original deionized water and the methanol in a certain ratio to form a mixed slurry 10. A plurality of zirconium beads 101 are used for mixing and grinding (step 510) to make the particle size less than 500 nanometers, wherein the rotation speed of the first ball mill 100 is 2800rpm±20%, the particle size of the zirconium beads 101 is 0.8 to 1.2mm, the filling rate is 65% to 80%, and the grinding time is 0.25 to 3 hours; the mixed slurry 10 is first placed in a first barrel A for stirring and then enters the first ball mill 100 for grinding, then enters a second barrel B for stirring and then enters the first ball mill 100 for grinding, and then enters the first barrel A, and repeats the above actions for repeated stirring and grinding, so that the mixed slurry 10 is completely ground. Preferably, the grinding time is 0.25 to 1.5 hours. The operating temperature is 15 to 30° C., preferably 15 to 25° C., to form the mixture particles 15. The solid content ratio in the mixed slurry 10 is 25 wt% to 40 wt%.
[0020] like Figure 2 As shown, an oil bath type vacuum concentrator 200 is used to perform an oil bath on the mixture particles 15 to remove the deionized water and the methanol (step 520).
[0021] The oil bath temperature is 120°C, the condensed water temperature in the oil bath vacuum concentrator 200 is 0 to 4 degrees, and the deionized water and the methanol in the mixture particles 15 are completely evaporated, and a plurality of microholes are generated on the surface of the mixture particles 15. These microholes increase the specific surface area of the mixture particles 15, which is beneficial to the next step of sintering adjustment and further increases the reaction rate and integrity.
[0022] Then the first stage of nitrogen-argon reaction operation is carried out, such as Figure 3 As shown, first, the mixture particles 15 obtained in step 520 are placed in a sintering furnace and sintered in a sintering environment with nitrogen and argon, wherein the ratio of nitrogen to argon is 98:2, and the temperature is increased to 500-700°C at a heating rate of 1 to 5°C per minute (preferably 2°C), and the mixture particles are heated at this temperature for 3 to 9 hours (preferably 6 hours) in an atmosphere simmering protection manner (step 530); wherein the atmosphere is replaced and replenished at a rate of 0.05L to 0.15L per minute.
[0023] At this time, the mixture particles 15 will undergo the first stage of oxygen-free (nitrogen-argon) reaction, that is, the zirconium source compound and the lanthanum source compound in the mixture particles 15 will react to produce La2Zr2O7 compound (zirconium-lanthanum compound) in this embodiment, and its chemical reaction formula (1) is:
[0024] 2ZrO2+La2O3→La2Zr2O7…………(1)
[0025] As described in the above equation, the molecular ratio of ZrO2 and La2O3 is 2:1. If the ratio is not as described above, the reaction can still occur, but the initial compound that has not reacted will remain in the final product, so the scope of this case still includes the mixture of various initial compounds in different ratios. The process in the above embodiment is illustrated by zirconium dioxide (ZrO2) and lanthanum oxide La2O3), but it is not used to limit the scope of the present invention.
[0026] like Figure 3 As shown, the zirconium-lanthanum compound (La2Zr2O7) is placed in a second ball mill 110 containing deionized water, and a lithium source compound (such as Li2CO3), a gallium source compound (such as Ga2O3), an aluminum source compound (such as Al2O3), and a lanthanum source compound (such as La2O3) are added. A plurality of zirconium beads 111 are used in the second ball mill 110 for mixing and grinding (step 540) to make the particle size less than 1000 nanometers, wherein the rotation speed of the second ball mill 110 is 2600rpm±20%, the particle size of the zirconium beads 111 is 0.5 to 0.8mm, the filling rate is 65 to 80%, and the grinding time is 0.5 to 2 hours; the method is to place the zirconium lanthanum compound into a first barrel C for stirring, then enter the second ball mill 110 for grinding, then enter a second barrel D for stirring, then enter the second ball mill 110 for grinding, and then enter the first barrel C, repeat the above actions and stir and grind repeatedly, so that the zirconium lanthanum compound is completely ground. Preferably, the grinding time is 0.5 to 1.5 hours and the operating temperature is 15 to 30°C, preferably, the operating temperature is 15 to 25°C, and small-sized mixture particles 20 are formed.
[0027] Then, the oil bath type vacuum concentrator 200 is used to perform the step of removing deionized water from the small-sized mixture particles 20 in an oil bath (step 550). The oil bath temperature is 120°C, the condensed water temperature of the vacuum concentrator is 0 to 4 degrees, and the deionized water in the small-sized mixture particles 20 is completely evaporated to form a small-sized mixture particle secondary agglomerate 22 (i.e., sintered powder), and a plurality of micro-holes are generated on the surface of the small-sized mixture particle secondary agglomerate 22. These micro-holes increase the specific surface area of the small-sized mixture particle secondary agglomerate 22, which is beneficial to the next step of sintering adjustment and further increases the reaction rate and integrity.
[0028] The lithium source compound is selected from one of lithium nitrate, lithium carbonate and lithium hydroxide. The gallium source compound is selected from one of gallium nitrate, gallium oxide and gallium hydroxide. The aluminum source compound is selected from one of aluminum oxide, aluminum hydroxide and aluminum nitrate.
[0029] The processes in the following embodiments are illustrated with zirconium dioxide (ZrO2), lanthanum oxide La2O3), lithium carbonate (Li2CO3), gallium oxide (Ga2O3), and aluminum oxide (Al2O3), but are not intended to limit the scope of the present invention. The processes described below are applicable to all combinations of compounds allowed in the five sources of the zirconium source compound, the lanthanum source compound, the lithium source compound, the gallium source compound, and the aluminum source compound in the previous paragraph.
[0030] Then, the second stage of aerobic reaction operation is performed, and the temperature of the small-sized mixture particle secondary agglomerate 22 is raised to 780 to 950° C., and then heated at this temperature in an "oxygen-rich environment" for 5 to 12 hours (preferably more than 6 hours). At this time, in the small-sized mixture particle secondary agglomerate 22, the remaining lithium source compound, the gallium source compound and the aluminum source compound will react with the lanthanum zirconium compound La2Zr2O7. In this embodiment, the three compounds of Li2CO3, Ga2O3, Al2O3 and O2 will react with the above-mentioned La2Zr2O7 in the second stage of aerobic reaction operation (step 560).
[0031] During the operation of the second stage reaction, the temperature is raised at a rate of 1 to 5°C per minute (preferably 2 to 4°C), and 1 to 3 liters of oxygen are added per minute for every 200g of the sintered powder until the temperature reaches 780 to 950°C, and the mixture is heated at this temperature for 5 to 12 hours (preferably more than 6 hours). At this time, the small-sized secondary agglomerates 22 of the mixture particles produced after the first stage nitrogen-argon reaction and the grinding of the second ball mill 110 will undergo the reaction of chemical reaction formula (2) to produce Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 , which has a cubic crystal structure. It can be used as a solid electrolyte for lithium batteries to conduct lithium ions. (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 Due to the addition of Ga and Al, compared with Li7La3Zr2O produced without adding Ga and Al 12 , its lithium ion equivalent ratio drops from 7 to 6.9 to 6.2. (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 The cubic crystal structure has larger channels, so the conduction rate of lithium ions can be increased.
[0032] Because the above prior art describes the conventional Li7La3Zr2O 12When it is a solid electrolyte between the anode and cathode of the battery, the conduction effect of its lithium ion channel on lithium ions is limited. Although it has a certain effect, it is still not comparable to liquid electrolytes. Therefore, it will limit the speed of lithium ion conduction, that is, limit the rate of charging and work.
[0033] The improvement method in this case is to add gallium oxide (Ga2O3) and aluminum oxide (Al2O3) to the conventional La2Zr2O7+Li2CO3+O2 reaction, so that Ga and Al replace Li7La3Zr2O 12 The part of Li in the (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 Particles, the Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 is a modified LLZO (Ga&Al doped LLZO). In this example, the five initial compounds of the zirconium source molecule, the lanthanum source molecule, the lithium source molecule, the gallium source molecule and the aluminum source molecule are reacted in the above two stages to produce a lithium lanthanum zirconium gallium aluminum molecular compound (Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 ) are all modified LLZO.
[0034] Its chemical reaction formula (2) is as follows:
[0035] 2La2Zr2O7+(7-x / 2-y / 2)Li2CO3+xGa2O3
[0036] +y Al2O3+La2O3→2Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 +7CO2………(2),
[0037] In Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 In Li7La3Zr2O, Ga and Al replace 12 Because Ga and Al have higher charge and atomic size, the entire Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12The formed cubic lattice, whose overall crystal structure can generate larger lithium-ion channels, thus accelerating the conduction rate of lithium ions in the solid electrolyte. Among them, the Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 particles will aggregate into the form of multiple agglomerates (i.e., Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 agglomerates 40, LLZO agglomerates 40), and each agglomerate contains multiple Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 formed cubic lattices.
[0038] In the above reaction, the molecular ratio of La2Zr2O7, Li2CO3, xGa2O3, y Al2O3, La2O3 is 2:(7 - x / 2 - y / 2):x:y:1. If the ratio is not the above, the reaction can still occur, but it will cause unreacted initial compounds to remain in the final product. Therefore, the scope of this case still includes mixtures of various initial compounds in different ratios. Among them, 0 < x < 0.8; 0 < y < 0.8; 0.1 < x + y < 0.8, and preferably 0 < x < 0.35; 0 < y < 0.45; 0.3 < x + y < 0.8.
[0039] In this case, the ratio of the mixed slurry formed by the zirconium source compound, the lanthanum source compound, the lithium source compound, the gallium source compound, and the aluminum source compound is the ratio corresponding to the respective molecular reaction coefficients in each reaction formula, so as to achieve a complete reaction; when the mixing ratio is not the ratio of complete reaction, the excess molecules will form impurities in the modified LLZO powder. Such operations of mixing in non-proportionate ratios to produce impurities are all within the scope of the rights of this case.
[0040] Then place the above-mentioned Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 agglomerates 40 into a jet mill 300. Among them, anhydrous ethanol (C2H5OH) is placed in the jet mill 300, and after adding Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 agglomerates 40, a solvent containing LLZO agglomerates is formed. The Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12The weight of the agglomerates 40 accounts for 25% to 45% of the total solvent containing the LLZO agglomerates.
[0041] In the air flow mill 300, a plurality of zirconium beads 301 are mixed and ground (step 570) to a particle size of less than 500 nanometers, wherein the rotation speed of the ball mill 300 is 3000 rpm ± 20%, the size of the zirconium beads 301 is 0.3 to 1.2 mm, the filling rate is 75 to 90%, the grinding time is 1.5 to 8 hours, preferably the grinding time is 2 to 5 hours, the operating temperature is 4 to 30° C., preferably the operating temperature is 8 to 20° C., and a smaller size of Li is formed. (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 Small block 42.
[0042] Then the Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 The fine block 42 is placed in a water bath vacuum concentrator 350 for water bath concentration at 40-60°C to remove the anhydrous ethanol; the condensed water temperature in the water bath vacuum concentrator 350 is 0 to 4 degrees; and finally LLZO fine powder 44 (lithium lanthanum zirconium oxide solid electrolyte (Lithium Lanthanum Zirconium Oxide; LLZO)) is obtained. The step of removing the anhydrous ethanol, such as drying and concentrating to room temperature, makes the small-sized Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 The anhydrous ethanol in the fine block 42 is evaporated. (Step 580)
[0043] In the first stage reaction, nitrogen and argon are added to form an atmosphere for simmering protection, and oxygen is added in the second stage reaction. The advantage is that nitrogen and argon are added in the first stage reaction, so that high-purity La2Zr2O7 can be produced. When the first stage reaction is complete and a uniform intermediate is formed, oxygen is added in the second stage reaction, and the reaction of chemical reaction formula (2) is purely carried out. In this case, the overall crystal structure formed is mainly composed of a cubic crystal structure. The crystal structure composed of a cubic crystal structure has a better efficiency in conducting lithium ions.
[0044] In order to speed up the reaction rate, the small-sized mixture particle secondary agglomerate 22 can be placed in a grid groove 50 before the second stage reaction operation. Figure 5As shown, the grid groove 50 is composed of multiple isolation grids 52 that divide a storage slot into multiple storage compartments 54, and then the small-sized mixture particle secondary agglomerates 22 produced after the first stage reaction and the first ball mill operation are placed in each storage compartment 54 respectively. Because the small-sized mixture particle secondary agglomerates 22 are dispersed in many tiny storage compartments 54, the reaction rate with oxygen is increased.
[0045] The advantages of this case are that in the first stage of the reaction, there are no lithium source molecules and oxygen environment, and nitrogen and argon form an atmosphere for simmering protection. Therefore, even if the internal particles react unevenly or are subjected to uneven temperature, the faster reaction to generate La2Zr2O7 will not further react with oxygen and lithium source molecules to form a mixed crystal phase in the next step, so that the first stage obtains a stable La2Zr2O7 intermediate phase; and in the second stage of the reaction, lithium source molecules and oxygen environment are added. Because the initial intermediate product has a stable and uniform phase, it can react evenly with the reactants to produce LLZO particles with a cubic lattice. In addition, because there is no traditional lithium salt (lithium source molecule) in the first stage, it avoids the lithium consumption caused by cumbersome or lengthy sintering; avoids phase degradation and disintegration caused by sintering due to variations in the equivalent number; and improves the process yield controllability and cost. Furthermore, in the second stage of the reaction operation, the small-sized mixture particle secondary agglomerate is placed in the grid slot. Because the small-sized mixture particle secondary agglomerate is dispersed in many tiny storage grids, the reaction rate with oxygen is increased.
[0046] In summary, the humanized and considerate design of this case is quite in line with actual needs. Its specific improvement of existing deficiencies is obviously a breakthrough in progress compared to the conventional technology, and it does have an improvement in efficacy, which is not easy to achieve. This case has not been published or disclosed in domestic and foreign literature and markets, and has complied with the provisions of the Patent Law.
[0047] The above detailed description is a specific description of a feasible embodiment of the present invention, but the embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the technical spirit of the present invention should be included in the patent scope of this case.
[0048] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for manufacturing a solid oxide electrolyte for a lithium battery, characterized in that: The following steps are involved: Placing at least one first salt compound into a first grinder, and then performing a first reduced pressure concentration, followed by a first stage oxygen-free reaction sintering operation; The first clump of compound is obtained, and then; The first agglomerated compound is mixed with at least one second salt compound, and placed in a second grinder, and then subjected to a second decompression concentration, followed by a second stage of aerobic reaction sintering operation to obtain a second agglomerated compound; Then, the second agglomerated compound is placed in a third grinder, and the grinder is subjected to a third reduced pressure concentration to obtain a final lithium battery solid electrolyte oxide.
2. The method for manufacturing a lithium battery solid oxide electrolyte according to claim 1, characterized in that: At least one of the first salt compounds is a zirconium source compound or a lanthanum source compound; and at least one of the second salt compounds is a lithium source compound, a gallium source compound, an aluminum source compound, or a lanthanum source compound. The lithium battery solid electrolyte oxide is a lithium lanthanum zirconium gallium aluminum molecular compound, namely LLZO.
3. The method for manufacturing a lithium battery solid oxide electrolyte according to claim 1, characterized in that: The first grinder and the second grinder are ball mills, and the third grinder is a jet mill.
4. The method for manufacturing a solid oxide electrolyte for a lithium battery according to claim 1, characterized in that: The first vacuum concentration and the second vacuum concentration are oil bath vacuum concentrations, and the third vacuum concentration is water bath vacuum concentration.
5. The method for manufacturing a solid oxide electrolyte for a lithium battery according to claim 1, characterized in that: The ball milling medium of the first grinding mill is deionized water and methanol, the ball milling medium of the second ball mill is deionized water, and the ball milling medium of the third ball mill is anhydrous ethanol.
6. A method for manufacturing a solid oxide electrolyte for a lithium battery, characterized in that: The following steps are involved: Step 500: Take a first ball mill, and add deionized water and methanol into the first ball mill; Step 510: Place two initial compounds, i.e., solids, of a zirconium source compound and a lanthanum source compound into the first ball mill, and mix and grind them with original deionized water and methanol in a certain ratio using a plurality of zirconium beads to form mixture particles, so that the particle size is smaller than a specific size; Step 520: drying the mixture particles through an oil bath vacuum concentrator, so that the deionized water and methanol in the mixture particles are evaporated, thereby generating a plurality of micropores in the dried mixture particles; Step 530: Perform the first stage nitrogen-argon reaction operation. First, place the mixed compound particles obtained in step 520 into a sintering furnace and continue to heat them in a sintering environment with nitrogen and argon. At this time, the mixed compound particles will undergo a chemical reaction under the protection of the first stage nitrogen and argon sintering to generate zirconium-lanthanum compounds. Step 540: placing the zirconium-lanthanum compound into a second ball mill containing deionized water, and adding a lithium source compound, a gallium source compound, an aluminum source compound, and a lanthanum source compound, and mixing and grinding the zirconium-lanthanum compound using a plurality of zirconium beads in the second ball mill to obtain small-sized mixture particles with a particle size of less than 1000 nanometers; Step 550: Then, the mixture is concentrated and dried in an oil bath vacuum concentrator, so that the deionized water in the small-sized mixture particles is completely evaporated, and a plurality of micropores are generated on the surface of the small-sized mixture particles, thereby forming a secondary agglomerate of the small-sized mixture particles, i.e., a sintered powder; Step 560: Perform the second stage of aerobic reaction operation. At this time, in the secondary agglomerate of the small-sized mixture particles, the remaining lithium source compound, gallium source compound, aluminum source compound, lanthanum source compound and O2 will perform the second stage of aerobic reaction operation with the zirconium lanthanum compound in the first stage reaction, and continue to heat and form modified lithium lanthanum zirconium gallium aluminum molecular compound particles, that is, modified LLZO particles; Because the gallium source compound and the aluminum source compound have higher charge and atomic size, the cubic lattice formed by the entire modified lithium lanthanum zirconium gallium aluminum molecular compound particles can produce a larger lithium ion channel, thereby accelerating the conduction rate of lithium ions in the solid electrolyte; wherein the modified lithium lanthanum zirconium gallium aluminum molecular compound particles will condense into a plurality of agglomerates, namely, LLZO agglomerates, each LLZO agglomerate containing a cubic lattice formed by a plurality of modified LLZO particles; Step 570: Then the LLZO agglomerate formed by the modified lithium lanthanum zirconium gallium aluminum molecular compound particles is placed in a jet mill for grinding to form a plurality of modified LLZO fine blocks, wherein anhydrous ethanol is placed in the jet mill and added to the modified LLZO agglomerate to form a solvent containing the LLZO agglomerate; Step 580: Then, the modified LLZO fine block is placed in a water bath vacuum concentrator for water bath concentration so that the anhydrous ethanol is evaporated to obtain the final LLZO powder; The zirconium source compound is selected from zirconium nitrate, zirconium dioxide, and zirconium hydroxide; the lanthanum source compound is selected from lanthanum nitrate, lanthanum oxide, and lanthanum hydroxide; the lithium source compound is selected from lithium nitrate, lithium carbonate, and lithium hydroxide; the gallium source compound is selected from gallium nitrate, gallium oxide, and gallium hydroxide; and the aluminum source compound is selected from aluminum oxide, aluminum hydroxide, and aluminum nitrate.
7. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: The zirconium source compound is zirconium dioxide (ZrO2), the lanthanum source compound is lanthanum oxide (La2O3), the lithium source compound is lithium carbonate (Li2CO3), the gallium source compound is gallium oxide (Ga2O3), and the aluminum source compound is aluminum oxide (Al2O3); Among them, the chemical reaction formula (1) of the first stage is: 2ZrO2+La2O3→La2Zr2O7…………(1), The second stage chemical reaction formula (2) is 2La2Zr2O7+(7-x / 2-y / 2)Li2CO3+xGa2O3 <h2 style=";text-align:left;direction:ltr">+y Al2O3+La2O3→2Li<h2 style=";text-align:left;direction:ltr"> (7-x / 2-y / 2) <h2 style=";text-align:left;direction:ltr"> Ga<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> Al<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> La3Zr2O<h2 style=";text-align:left;direction:ltr"> 12 <h2 style=";text-align:left;direction:ltr"> +7CO2………(2), Modified LLZO is Li (7-x / 2-y / 2) Ga x Al y La3Zr2O 12 .
8. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 7, characterized in that: In the chemical reaction formula (1) of the first stage, the molecular ratio of ZrO2 and La2O3 is 2:1, and in the chemical reaction formula (2) of the second stage, the molecular ratio of La2Zr2O7, Li2CO3, xGa2O3, yAl2O3, and La2O3 is 2:(7-x / 2-y / 2):x:y:1, where 0 <x<0.8;0<y<0.8;0.1<x+y<0.8。 9. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: The solid content in the mixed slurry consisting of deionized water, methanol and solids is 25wt% to 40wt%.
10. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: In step 510, the specific size of the particles of the mixed slurry is less than 500nm, the rotation speed of the first ball mill is 2800rpm±20%, the size of the zirconium beads is 0.8 to 1.2mm, the filling rate is 65 to 80%, the grinding time is 0.25 to 3 hours, and the operating temperature is 15 to 30°C.
11. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: The ratio of nitrogen to argon in step 530 is 98:
2.
12. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: In step 530, the first step of the nitrogen-argon reaction operation is performed at a heating rate of 1 to 5°C per minute until the temperature reaches 500 to 700°C, at which temperature the mixture particles are simmered for 3 to 9 hours, wherein the atmosphere is replaced and replenished at a rate of 0.05L to 0.15L per minute.
13. A method for manufacturing a lithium battery solid oxide electrolyte according to claim 6, characterized in that: In step 540, the rotation speed of the second ball mill is 2600 rpm ± 20%, the particle size of the zirconium beads is 0.5 to 0.8 mm, the filling rate is 65 to 80%, the grinding time is 0.5 to 2 hours; and the operating temperature is 15 to 30°C.
14. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: When the second stage aerobic reaction operation is performed in step 550, the temperature of the secondary agglomeration of the small-sized mixture particles is raised to 780 to 950° C., and then heated at this temperature for 5 to 12 hours in an “oxygen-rich environment”.
15. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: In step 560, the weight of the modified LLZO agglomerates accounts for 25% to 45% of the total solvent containing the LLZO agglomerates; In the air flow mill, a plurality of zirconium beads are used for mixing and grinding to make the particle size less than 500 nanometers, wherein the rotation speed of the air flow mill is 3000rpm±20%, the size of the zirconium beads is 0.3 to 1.2mm, the filling rate is 75 to 90%, the grinding time is 1.5 to 8 hours, and the operating temperature is 4 to 30°C to form smaller-sized modified LLZO blocks; and then a water bath type vacuum concentrator is used for water bath concentration to obtain modified LLZO powder, so that the anhydrous ethanol in the small-sized modified LLZO blocks is evaporated.
16. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 7, characterized in that: In the second stage reaction of step 550, the temperature is increased at a rate of 1 to 5° C. per minute, and 1 to 3 liters of oxygen are added per minute for every 200 g of the sintered powder until the temperature reaches 780 to 950° C., and the mixture is heated at this temperature for 5 to 12 hours. At this time, the small-sized compound particles formed after the first stage nitrogen-argon reaction and the second ball mill grinding will undergo a secondary agglomeration reaction of chemical reaction formula (2) to produce modified LLZO, which has a cubic crystal structure. It can be used as a solid electrolyte for lithium batteries to conduct lithium ions; The first stage reaction is a nitrogen-argon reaction, and oxygen is added in the second stage reaction. The purpose is to produce a high-purity zirconium-lanthanum compound in the first stage reaction and a cubic lattice modified LLZO in the second stage reaction.
17. A method for manufacturing a lithium battery solid oxide electrolyte according to claim 6, characterized in that: Before the second stage reaction, the small-sized mixture particles are secondary aggregated and placed in a grid trough for the second stage reaction, wherein the grid trough is composed of a plurality of isolation grids, which divide a storage tank into a plurality of storage compartments, and then the small-sized mixture particles are secondary aggregated 22 and placed in each storage compartment respectively, because they are dispersed in many tiny storage compartments, so as to increase the reaction rate with oxygen.
18. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: The ratio of the mixed slurry formed by the zirconium source compound, the lanthanum source compound, the lithium source compound, the gallium source compound, and the aluminum source compound is the ratio corresponding to the reaction coefficient of each molecule in each reaction formula, so as to achieve a complete reaction; when the mixing ratio is not a complete reaction ratio, excess molecules will form impurities in the modified LLZO powder.
19. A method for manufacturing a lithium battery solid oxide electrolyte according to claim 6, characterized in that: In step 510, the stirring and grinding method is to place the mixed slurry into the first barrel A for stirring and then into the first ball mill for grinding, then into the second barrel B for stirring and then into the first ball mill for grinding, and then back to the first barrel A, repeat the above actions for repeated stirring and grinding, so that the mixed slurry is evenly and completely ground.
20. The method for manufacturing a solid oxide electrolyte for a lithium battery according to claim 6, characterized in that: The temperature of the oil bath in step 520 is 120°C, and the temperature of the condensed water in the oil bath type vacuum concentrator is 0 to 4°C.
21. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: In step 540, the stirring and grinding method is to place the zirconium-iridium compound into the first tank C for stirring and then into the second ball mill for grinding, then into the second tank D for stirring and then into the second ball mill for grinding, and then into the first tank C again, and repeat the above actions to stir and grind repeatedly, so that the zirconium-iridium compound is evenly and completely ground.
22. A method for manufacturing a solid oxide electrolyte for lithium batteries according to claim 6, characterized in that: The temperature of the oil bath in step 550 is 120°C, and the temperature of the condensed water in the oil bath type vacuum concentrator is 0 to 4°C.